The impacts of sports facilities development on the urban growth of Kuala Lumpur federal territory, Malaysia / Dasimah Omar and Maassoumeh Barghchi - Omar, Dasimah; Maassoumeh, Barghchi (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2010)
There is currently tremendous interest in sport in Malaysia. Sport in Malaysia is only considered as an industry in the last ten years. Sports facilities have improved rapidly over the past years. However, such improvements are inadequate compared to the overall development of sports at international level. On the other hand, recent development of sports facilities provide new role in cities to catalyse new development or regenerate decaying area of the cities whether to provide better justification for public investment due to requirement of huge money for construction, ancillary needs and constant maintenance cost. In Malaysia, increase in the amount of public money being spent on sports facilities, at the same time, increase in the number of sports facilities necessitate demand to investigate issues surrounding sports facilities development especially in Kuala Lumpur as the regional and national centre for sporting activities. The aim of this research was to explore the existing sports facilities in Kuala Lumpur federal territory developed by Kuala Lumpur City Hall (KLCH) and to compare the effectiveness and benefits through residents' perception. The research investigated the development of the all sports facilities developed by KLCH in Kuala Lumpur. The relationship between sports facilities and urban areas identified through sports facilities managers' perception. The research also examined the four case studies each selected from one of the four managing zones of sports facilities developed by KLCH based on the residents' perception. The impacts and intangible benefits were analysed and the research was able to compare the effectiveness and benefits of the case studies. The findings revealed that land availability is the most important factor for selecting the location of sports facilities in Kuala Lumpur. Lack of public transportation and design factors are considered as the problems through managers' perception. In addition, lack of activities and public use. The results from the residents' perceptions survey demonstrated that the people who use the sports facilities are not staying only close to the facilities. They have better attitude about facilities than programmes. The result from applying contingent valuation method revealed very limited intangible benefits and impacts. People are not sure to receive benefits from the presence of sports facilities. The research able to rank the case studies based on residents' perception towards their attitude about facilities and programmes, using of the facilities, intangible benefits and impacts. The Bangsar Sports Complex was ranked the best, followed by Titiwangsa Stadium, Taman Tun Dr Ismail Community Centre and Swimming Complex, respectively. The findings show that there is a need to improve and increase the impacts and benefits in sports facilities development in the future.